Privacy protection in cloud computing with homomorphic encryption - Khor, Chin Yeow (2019)
Homomorphic encryption is a technique that allows the computation of data on the cloud which does not require any decryption of data. This encryption leads to increasing in the security of data as outsiders only able to obtain the encrypted data. However, recent homomorphic encryption scheme was running very slow, which had drastically decrease in its performance. There are a lot of approaches on increase the speed of encryption to increase its performance and become more practical. One of the approaches is by using FPGA (Field-Programmable Gate Array) board. The FPGA is an integrated circuit that being design and configured by a designer or customer after manufacturing, hence come with the term “field-programmable”. The FPGA have large resources of logic gate and block RAM and advantage of pipeline architecture for parallel computation. This project will focus on the implementation of homomorphic encryption on FPGA board.